Relative performance evaluation and the level playing field - Baldenius, Tim; Li, Jing; Qiu, Lin (Review of Accounting Studies, 2026)
Relative performance evaluation (RPE) is widely used to filter out common shocks, but it is prone to collusion. We study the performance of RPE when agents are differentially productive (or evaluated in a biased manner). While such diversity is always costly in a static setting, it can be useful in repeated interactions, because it makes it harder for agents to collude. We identify conditions under which the principal prefers independent or joint performance evaluation if agents are identical but prefers RPE if they are diverse. In low-skill industries, the principal should offer asymmetric contracts even to homogeneous agents—a form of favoritism—as the cheapest way to combat collusion. Our results generate novel empirical predictions and contribute to the recent literature linking accounting and labor economics.